EFEKTIVITAS E-GOVERNMENT DALAM MEWUJUDKAN SMART CITY DI KOTA BEKASI - HAMLUDDIN HAMLUDDIN (Interpretasi: Communication & Public Relations, 2021)
Bekasi City is a buffer zone in the eastern part of Jakarta which is very busy withactivities. This requires the local government to make efforts so that work programs can be implemented in accordance with what is needed by the community. One of the policies in realizing e-government is about managing information to the public. Bureaucratically, the Mayor of Bekasi, Rahmat Effendi, formed a Public Relations in charge of managing information which is then conveyed to the public. In line with the changing pattern of society to the digital era, the Bekasi City Government has made a policy that integrates all data and information into a system that can be connected to the community. This program is named Bekasi Smart City or smart city. This program is carried out to achieve the goal of maximizing service to the community.